Without a law or a technical body? The institutional framework for disaster risk management in the response to the 2016 earthquake in Ecuador - Cahueñas Muñoz, Hugo (2018)
The article studies the Ecuadorian legal framework related to disaster risk management in two moments. First, it describes the legal framework that existed prior to the earthquake of April 16, 2016 (16A); and, secondly, the legal framework generated from decrees issued in response to the earthquake is analyzed. Based on this analysis, it is concluded that the response actions to 16A were not fully adapted to the existing legal framework, on the contrary, an over position of functions and institutions was presented. Consequently, bearing in mind the mandate of the constituent power and the state obligation to protect individuals, communities and the nature of the negative effects of disasters, Ecuador must adopt a risk management law that adapts the dispersion of standards and institutions, fill the legal gaps, and solve the unconstitutionality due to the lack of legislative adaptation.